Smart Home Control Prototype Based on Internet of Things Using Google Assistant (Program Studi Pendidikan Teknologi Infromasi UMK, 2025)
Smart home technology allows users to control household electronic devices automatically and remotely, including through voice commands. This study aims to design and develop a smart home control prototype based on the Internet of Things (IoT) using Google Assistant to control devices such as lights and fans. The system utilizes a NodeMCU ESP32 as the microcontroller, a 4-channel relay module as an automatic switch, and the Sinric Pro cloud service to connect voice commands from Google Assistant to the hardware. The research follows the ADDIE development model, which includes analysis, design, development, implementation, and evaluation stages. The test results show that the system can receive and execute voice commands with high accuracy in both Indonesian and English. However, the system still has limitations, such as dependence on a stable internet connection. Overall, this prototype functions well and has the potential to be further developed. In the Google Assistant analysis obtained from this system, Conversion and Calculation have the highest accuracy rate with 96.7%, while Voice command is the lowest with 85.3%.